The effect of work motivation and teamwork on employee performance at KSP prima sejahtera mulyo - Didimus Jegani; Arif Hidayat (Jurnal Mantik, 2026)
The dynamic capacity of human resources plays a crucial role in the operational sustainability of cooperative institutions. This study aims to analyze the partial and simultaneous effects of work motivation and teamwork on employee performance at Koperasi Simpan Pinjam Prima Sejahtera Mulyo (KSP Prima Sejahtera Mulyo). Based on initial observations from January to September 2025, the cooperative faced a performance gap of 11.20% in billing targets accompanied by sharp monthly fluctuations. Using a descriptive quantitative method, primary data was collected through a 1–5 Likert scale questionnaire to 37 employees as a saturated sample (census). Data analysis used multiple linear regression through IBM SPSS. The results of the classical assumption test confirmed that the residual data were normally distributed, free from heteroscedasticity, and there was no multicollinearity. Partial testing showed that work motivation (X1) had a positive and significant effect on performance (t count = 6.408; p = 0.000). Teamwork (X2) also had a positive and significant effect (t count = 3.166; p = 0.003). Simultaneously, both variables had a significant effect (F count = 174.575; p = 0.000). The coefficient of determination (R2 = 0.911) proves that 91.1% of the performance variation is explained by motivation and teamwork. Cooperative management is advised to evaluate the reward system periodically and implement a structured team building program